Contemporary Changes in Islamic Higher Education in Indonesia: Dynamic Encounter Between Modernisation and Tradition - Hayadin, Hayadin; Niam, Khoirun; Munawiroh,; Lukens-Bull, Ronald (Journal of Al-Tamaddun, 2025)
The primary mandate of Islamic higher education in Indonesia, upon its establishment, was to preserve Islamic sciences and counter secularism. However, the transformation of IAIN into UIN in 2000 introduced a curriculum that integrated modern sciences, often categorized as secular due to their focus on worldly and nonreligious matters. This study explores how this shift occurred and its implications for Islamic educational institutions in Indonesia. Using historical analysis of institutional legacies, documentary reviews, and the biographies of reformist thinkers, the findings reveal that this transformation was a gradual evolutionary process influenced by alumni educated in Western contexts. The shift in educational orientation from solely religious to broader scientific disciplines is not inherently secularizing but reflects an effort to reconcile modern sciences within an Islamic framework. Challenges in this process include the failure to produce ‘ulamā’, which traditionalist responses addressed by establishing Ma’had ‘Alī, institutions dedicated to Islamic sciences. Consequently, Islamic higher education in Indonesia today manifests in two forms: institutions that integrate modern sciences within an Islamic worldview and those that exclusively preserve traditional Islamic knowledge.